ECOTOURISM BUSINESS COMPETENCE IN CREATING COMMUNITY INCOME - Ketut Irianto; Ni Nyoman Aryaningsih; Ni Ketut Masih; Made Bagiada (Jurnal Internasional Ilmu Pengetahuan Terapan bidang Pariwisata dan Events, 2017)
The economic development of a region is determined by the increase of contribution of economic sector activity. The tourism sector is one of the economic sectors that has an important role in and is able to grow the regional economy. Sustainability of the tourism sector of the economy can not be separated from the role of environmental resources as tourism attractions (objects). This study is to analyze ecotourism business competence in creating income of community. The study is designed in a descriptive-quantitative way. The collection of data used is observation and interview. The data used is descriptive-quantitative in order to determine and analyze the ecotourism business competence and its impact on improving income of community. The results show that the strategy to achieve an income community must be supported by having business competence based on ecotourism. Business competence is dominated by social competence in creating people’s income in the tourism sector, yet less attention to other competencies. Ecotourism development is done by building the overall business competence and network of cooperation between the parties concerned.